2009
DOI: 10.1089/jwh.2008.1067
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Characteristics of Vaginal Microbicides in Women with Bacterial Vaginosis

Abstract: Background: Vaginal microbicides have the potential to reduce HIV=STD acquisition when used consistently. Our objectives were to determine product attributes associated with willingness to use a vaginal microbicide and whether product preferences varied according to participant characteristics. Methods: Women (n ¼ 408) with bacterial vaginosis (BV) were recruited as part of a randomized trial to prevent BV. Participants completed a survey interview that assessed demographic information, sexual history, and dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Research involving women in the United States [20], Malawi [21], Zimbabwe [22,23] and China [24] has shown high acceptance of microbicide products among study populations. A 2005 review on microbicide acceptability indicated that, at the time, 77% (41 out of 53) of acceptability studies collected data on physical characteristics of products including odor, color, texture and viscosity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Research involving women in the United States [20], Malawi [21], Zimbabwe [22,23] and China [24] has shown high acceptance of microbicide products among study populations. A 2005 review on microbicide acceptability indicated that, at the time, 77% (41 out of 53) of acceptability studies collected data on physical characteristics of products including odor, color, texture and viscosity [25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the vaginal microbial ecosystem is more stable when dominated by a prevalence of L. crispatus compared to those dominated by L. iners or a mixture of lactobacilli (France et al, 2016 ). Recent studies identify several bacterial species as biomarkers of cervical-vaginal microflora to improve both accuracy of infertility diagnosis and therapeutic procedures (Cook et al, 2009 ; Campisciano et al, 2017 ). L. iners , in particular, is described as an important biomarker of vaginal microbiota health able to predict the outcome of Assisted Reproductive Technology (ART) (Tärnberg et al, 2002 ; Vásquez et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…They have different spectra of antimicrobial activity but equivalent efficacy with regard to short-term and long-term cure rates [ 15 , 23 , 34 – 36 ]. Oral therapy with metronidazole is usually preferred over vaginal application according to the various guidelines; however, due to its metabolism in the liver it is associated with frequent gastro-intestinal side effects [ 27 , 35 , 37 39 ]. Clindamycin is usually recommended in the form of a vaginal cream.…”
Section: Introductionmentioning
confidence: 99%